Effect of Indol Butyric Acid (IBA) on the Growth of Dragon Fruit Cuttings (Hylocereus costaricensis) - fansaidha, Siswa Panjang Hernosa (Talenta Publisher, 2020)
The difficulty of root formation cuttings dragon fruit plants is influenced by several factors; The first disease that often occurs is a rotten stem. This disease usually strikes in early planting dragon fruit, dragon fruit plants often have decay at the base of the stems, there are brown and white fur. The decay caused by excessive soil moisture so it appears that the fungus that causes rot (Sclerotium rolfsii sacc). Both the stem to rot can also be caused when the rod directly planted, the sap is still wet rot can give effect to the dragon fruit cuttings. One attempt to increase the percentage growth of cuttings is using Indol Butyric Acid (IBA), which is a type of plant growth regulator that is used to stimulate root formation. The aim of this study was to investigate the effect of indole butyric acid (IBA) on the growth of stem cuttings of red dragon fruit (Hylocereus costaricensis). This research was conducted at the village Sidorukun, District Pangkatan, Labuhan Batu Regency, with a height of ± 39 m asl, from July to September 2016. The research design used in this study is a randomized block design with 5 treatments the concentrations of the hormone IBA consists of A0: 0 ppm, A1: 4000 ppm, A2: 5000 ppm, A3: 6000 ppm, A4: 7000 ppm and 5 replicates so that there are 25 total plot trials. Parameters observed that the percentage of the emergence of shoots, age appeared shoots, shoot length (cm), fresh weight of shoots (g), dry weight of shoots (g), root length (cm), fresh weight of the root (g), the volume of roots (g), root dry weight (g). Data were analyzed using linear models continued with Duncan test. The results obtained showed that the administration of Indole butyric acid (IBA) significantly affected the percentage of observation parameters appear buds, shoots emerging age, number of shoots, root length, fresh weight of root, root volume, and root dry weight. But it did not affect the parameters of observation shoot length, fresh weight of shoots, and buds dry weight. Keywords: dragon fruit plants (Hylocereus costaricensis), Indole butyric acid (IBA), cuttings, growth. References Anita, 2008. Kajian Media Tanam dan Konsentrasi BAP (Benzyl Amino Purin) Terhadap Pertumbuhan Setek Tanaman Buah Naga Daging Putih (Hylocereus undatys).Universitas Sebelas Maret. Febriana, S.2009. Pengaruh konsentrasi ZPT dan Panjang Setek terhadap Pembentukan Akar dan Tunas pada Setek Apokad (Persea Americana Mill). Skripsi Pertanian Bogor. Bogor Hasanah, F. dan Setiari, N. 2007. Pembentukan Akar Pada Stek Batang Nilam (Pogostemon cablin Benth.) Setelah Direndam Iba (Indol Butyric Acid)Pada Konsentrasi Berbeda. Buletin Anatomi dan Fisiologi Vol. 15. No. 2. Hal. 1-6. Kartina, B., Ashar, T., dan Hasan, W. 2013. Karakteristik Pedagang, Sanitasi Pengolahan dan Analisa Kandungan Rhodamin B pada Bumbu Cabai Giling di Pasar Tradisional Kecamatan Medan Baru Tahun 2012. Lingkungan dan Kesehatan Kerja, 1(2): 1-7. Novitasari, B, Meiriani, Haryati 2015. Pertumbuhan Setek Tanaman Buah Naga (Hylocereus costaricensis (Web.) Britton & Rose) dengan Pemberian Kombinasi Indole Butyric Acid (IBA) dan Naphthalene Acetic Acid (NAA). Jurnal Agroekoteknologi, E-ISSN No. 2337- 6. Vol.4. No.1, Desember 2015. (564) :1735 – 1740. Prastowo, N. H., J, M. Roshetko dan G. E. S Manurung 2006. Tehnik Pembibitan dan Perbanyakan Vegetatif Tanaman Jarak pagar ( Jatropha curcas L.) dengna Setek Batang. Pengaruh Panjang dan Diameter Setek. Buletin Agronomi (36) (3) ;255_262). Purwati, MS. 2013. Pertumbuhan Bibit Buah Naga (Hylocerrus costaricensis) Pada Berbagai Ukuran Setek Dan Pemberian Hormon Tanaman Unggul Multiguna Ekslusive. Jurnal Online Agroekoteknologi. 2(5) 2805-3548. Ramadiana, S. 2008. Respon Perumbuhan Setel Sanseveria trifasciata var. laurentii pada pemberian konsentrasi IBA dan asal bahan tanama (skripsi). Lampung; Jurusan Budidaya Pertanian, Universitas Lampung. Ramadiana S, 2008. Respon Pertumbuhan Stek Lidah Mertua (Sansevieria trifasciata var. Lorentii) pada Pemberian Berbagai Konsentrasi IBA dan Asal Bahan Tanam. www.unila.ac.id. Jurnal vol 6.281 Rineksane, I A dan Sukarjan, M, 2015. Regenerasi Anggrek Vanda tricolor Pasca Erupsi Merapi Melalui Kultur In Vitro. Seminar Nasional Universitas PGRI Yogyakarta 2015. ISBN 979-602-73690-3-0. Rugayah, Anggalia, Ginting, 2012. Pengaruh Konsentrasi dan Cara Aplikasi IBA (Indole Butiric Acid) terhadap Pertumbuhan Bibit Nanas (Ananas comosus [L] Merr). Asal Tunas Mahkota. Jurnal Agrotropika 17 (1):3-38) Salisbury, F.B. dan Ross, C.V. 1995. Fisiologi Tumbuhan Jilid 3 Bandung: ITB Press. Suryaningrum, R, dkk, 2016. Analisis Pertumbuhan Beberapa Varietas Kedelai pada Perbedaan Intenssitas Cekaman Kekeringan. Agrosains 18(2); 33-37, 2016; ISSN; 1411-5786. Santoso, U dan F. Nursandi 2001. Kultur Jaringan Tanaman. Universitas Muhammadiyah Malang. Press. Malang. Shofiana, A., Rahayu, Y S, Budipramana, L, S, 2013. Pemberian beberapa konsentrasi IBA (Indole Butiryc Acid) Pada Pembentukan Akar Setek Tanaman Buah Naga. Jurnal Lentera Bio Vol. 2 No.1 Januari 2013;101-105. ISSN : 2252-3979 Seran. H. T dan Thiresh. A. 2015. Root and Shoot Growth of Dragon Fruit (Hylocereus undatus) Stem Cutting as Influence by indole Butyric Acid. Agricultural and Biological Sciences Journal Vol, 1 No, 2 2015. American Institue of Science. Yunanda Jhon Murniati, Yoseva Sri. 2015. Pertumbuhan Setek Batang Tanaman Buah Naga (Hylocereus costaricensis) Dengan Pemberian beberapa Konsentrasi Urin Sapi. JOM Faferta Vol 2. No. 1 Februari 2015. UNRI.